Viability Assay Of Human Fibroblast Cells Treated by Water Hyacinth Leaf Extract After 24 Hours Incubation - Ully Nafisah Wardi (Journal of Stem Cell Research and Tissue Engineering, 2021)
Inflammation and alveolar bone resorption are indications of periodontal disease, which is a chronic inflammatory illness caused by bacterial colonization that damages the soft and hard structures that support the teeth. In response to persistent tissue injury and chronic inflammation, fibroblasts also play a role in the synthesis and maintenance of extracellular matrix, cell proliferation, and cell differentiation. Fibroblasts play a crucial part in the healing of wounds. Phenols, alkaloids, flavonoids, and tannins are some of the health-promoting components found in water hyacinth. As a result, plant extracts must be tested first, one of which is the viability test in accordance with the requirements and materials in the field of dentistry. The viability test is a cell-based test that is often used for screening compounds to determine whether the test compound has an effect on cell proliferation or has a direct cytotoxic effect that leads to cell death. The goal of this study is to figure out what concentration of water hyacinth leaf extract can keep human gingival fibroblast cells alive for 24 hours. Primary cell cultures from human gingiva were extracted and placed in a 96-well microplate. For 24 hours, water hyacinth leaf extract at concentrations of 1 mg/ml, 0.5 mg/ml, 0.25 mg/ml, 0.25 mg/ml, 0.125 mg/ml, 0.0625 mg/ml, 0.0312 mg/ml, 0.0156 mg/ml was administered to each well in the microplate. After 24 hours of incubation, the MTT assay was carried out by adding MTT solution. The optical density of formazan was measured using an ELISA reader at a wavelength of 590 nm, and viability was calculated using the viability formula. Starting at 0.125 mg/ml, 0.0625 mg/ml, 0.0312 mg/ml, and 0.0156 mg/ml, the vitality of human gingival fibroblast cells was good. In the treatment group, the greatest vitality of human gingival fibroblast cells was 0.0156 mg/ml (75.98%).